The Impact of Export Goods and Services on Iraq's Gross Domestic Product from 1972 to 2022 - Hussein, Araz Waleed; Tasar, İzzet (Journal of Danubian Studies and Research, 2023)
This study aims to investigate and analyze the effects of exports of goods and services on GDP and the relationship between exports of goods and services and GDP from 1972 to 2022 in Iraq using annual data from the World Bank database. This study suggests having a positive impact of exports of goods and services on GDP and intended to have a long-run relationship between exports of goods and services and GDP. According to the results of the Least Squares Model which show that exports of goods and services have a positive impact on GDP. According to the results of the Johansen Cointegration Test, there is a long-term relationship between exports of goods and services and GDP in the Iraqi economy from 1972 to 2022.